Sistem Informasi Akademik Berbasis Web : Studi Kasus SMK Asshiddiqiyah Garut - Setiawan, Ridwan; Rahayu, Sri; Darul Ikhrom, Taufik (Jurnal Algoritma, 2025)
The management and access to academic information at SMK Asshiddiqiyah Garut is still ineffective. The student assessment process requires re-recording in Microsoft Excel for each subject, which is time-consuming and prone to recording errors. In addition, parents find it difficult to obtain information on learning outcomes because they have to come directly to the school. The purpose of this study is to design and develop a web-based academic information system that can make it easier for students, parents, and teachers to manage and obtain academic information online. The software development methodology uses the Rational Unified Process with the stages of inception, elaboration, construction, and transition. The resulting system was tested using blackbox testing, and the test results showed a satisfaction level of 95.7% (strongly agree category) from students and 78.7% (agree category) from teachers.